Media Representation of Pakistani Transgender People in Newspapers’ Blogs Through Corpus Approaches - Zahra, Tehseen; Abbas, Akhtar (Italian Sociological Review, 2024)
Media (mis)representation of transgender people has become crucial in shaping the perception, attitude and behaviours of the masses towards them all over the world. Pakistani media is not an exception regarding the portrayal of transgender individuals living in Pakistan. The current study focuses on revealing media representation of Pakistani trans people through blogs published in the country. The current study employs corpus approaches to explore this representation of transgender identity by analysing newspapers’ blogs published on the subject (i.e. on transgender people) in Pakistan. The concordance lines of the first ten recurrent content words including transgender, community, people, rights, Pakistan, gender, society, persons, government, and identity from the word list were analysed to explore the themes related to the identity of transgender people in the country. The study found linguistic expressions of transgender apartheid in Pakistan at all levels of the social fabric of the country. However, at the same time discourse of solidarity towards transgender identity was also noticed in the data of the current study. The study proffers an insight to the linguists in general and corpus linguists, in particular, to extend theoretical conceptualization, application of linguistic methods and corpus linguistic techniques to highlight the issues/problems faced by transgender people.